البعد الإقليمي للأزمة الليبية وفق منظور مدرسة كوبنهاغن - نوال, بومليك (جامعة الوادي.University eloued, 2021)
تعد مدرسة كوبنهاغن لأبحاث الامن والسلام من أبرز المدارس التي قدمت اسهامات نظرية في توسيع مفهوم الامن،في هذا الإطار كان لباري بوزان “Barry buzan”وأول ويفر Ole Weaver "دور بارز في التأسيس لبناء تصور أمني جديد،فبالإضافة إلى توسيع قطاعات الامن ونظرية الامننة نجد إسهاماتهم النظرية الخاصة بالتفسير البعد الإقليمي للأمن (نظرية مركب الامن الإقليمي)،الذي يعتبر إقليمية الأمن ظاهرة علائقية،كون الأمن علائقي فلا يمكن إدراك الأمن القومي لأي دولة بعيدا عن محيطها الإقليمي.من هذا المنطلق واعتمادا على أبرز الإسهامات النظرية الخاصة بتفسير البعد الإقليمي للأمن يتساءل المقال عن العلاقة بين الأزمة الليبية وعدم الاستقرار في المنطقة،حيث تعتبر الأزمة الليبية من أبرز الأزمات التي ضربت الأمن الإقليمي وهو ما يشكل تهديد للأمن القومي لدول الجوار. The Copenhagen School of Security and Peace Research is one of the most prominent schools that have made theoretical contributions to the expansion of the concept of security , In this context, “barry buzan” and “Ole Weaver” had a prominent role in establishing to build a new security perception. In addition to expanding the security sectors and security theory, we find their theoretical contributions to the interpretation of the regional dimension of security complex (regional security complex theory),which is considered regional security though a Relational phenomenon, since the security is relational, the national security of any country is not perceived far from its regional environment. From this standpoint and based on the most prominent theoretical contributions to the interpretation of the regional dimension of security, the takles research the relationship between the Libyan crisis and instability in the region, where the Libyan crisis is one of the most prominent crises that It hit regional security, which poses a threat to the national security of neighboring countrie
The Regional Dimension Of The Libyan Crisis According To Copenhagen School Perspective
مجلد 12 العدد02
Keywords: مدرسة كوبنهاغن؛ الأمن الإقليمي ؛نظرية مركب الأمن الإقليمي؛الأزمة الليبية; Copenhagen School; Regional security; Security compound; Libyan